If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(3d+3)+(3d+3)=4d+6+2d
We move all terms to the left:
(3d+3)+(3d+3)-(4d+6+2d)=0
We add all the numbers together, and all the variables
(3d+3)+(3d+3)-(6d+6)=0
We get rid of parentheses
3d+3d-6d+3+3-6=0
We add all the numbers together, and all the variables
=0
d=0/1
d=0
| -7(y+10)-11=-88 | | 7x-4=-2x+1+9x=-5 | | 11+4x-8=27 | | 6(d+6)=4d+6+2d | | 50+5m=85-2m | | 3-2(x+8)=-15 | | x*0.15=35 | | 3a+4=-2a+9 | | -4y+6=35y-3 | | 4x+1/2(8x+)=2(4x+3 | | 17-2p=2p-5-2p | | 2y+9=8y+29 | | 4g-2=2g+8 | | 3+4x=-2x-9 | | -7n+6n=-7-5 | | 4a+2a=180 | | -3k-2=2*k+2 | | -9=c+-8 | | 12u+2=7u+22 | | 6u-3u+5=20 | | -2z+3=7 | | -2=(1/x+3) | | 0.5h-1=0.4h+5 | | 6/4x+x=12 | | 16s+-4s+-19=5 | | F(x)=2x+x/3 | | 4(5-2x)=-4 | | 135-5x=90 | | 16x+4=2x-8 | | 9r-10r-11r+-20=-8 | | 3/4(9x+15)-7x=45 | | N—-4=16,n |